V-V ECMO Vascular Cannula Problems: 3 Case Report - Murat Aslan; Rabia Yılmaz; Mehmet Süleyman Sabaz; Zafer Çukurova (Galenos Yayinevi, 2022)
The vascular cannulation step is of great importance for the effective and safe implementation of extracorporeal membrane oxygenation (ECMO) support. We experienced various problems associated with ECMO vascular cannulation (malposition, thrombosis, recannulation, collapse) in 3 patients who developed coronavirus disease-2019 acute respiratory distress syndrome and received veno-venous ECMO support, and here we share our experience in their management. Appropriate vascular cannula size, vascular cannula structure, selection of the vascular cannulation site, and precise vascular cannulation can make ECMO support more effective and reliable.